KESESUAIAN LAHAN UNTUK TANAMAN PERTANIAN DAN PRODUKSINYA DI KECAMATAN PONJONG KABUPATEN GUNUNGKIDUL - , Fajar Sulantika Suma ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The increasing human needs in line with the increasing demand for land, so there is competition in the use of land for both agricultural and non agricultural. Land evaluation research to demonstrate the production constraints of a commodity in a region. Land evaluation requires the availability of climate data, soil physical condition and other environmental fields, as well as requirements of land use (land use requirements) and requirements for growing plants (crop requirement). This research was conducted to determine the level of land suitability and productivity of agricultural crops to corn, peanut and soybean, which is a prospective commodities and commodities. The research was conducted in the area of Gunung Kidul District District Ponjong DIY. Determining the location of the sample observations were made by random sampling, the samples taken were 24 respondents, with land units as stratanya, based on slope class, land forms, soil types and land use. Results showed there were 48 land units. Assessment of suitability of land suitability produce S3, N1, and N2. While limiting factor in this study were rooting depth (r), nutrient content (n), potential for mechanization (m), land slope (s), the threat of erosion (e). Remains a limiting factor to note is the presence of karst hills monoklinal and dome which should be preserved as a conservation rather than cultivation area. Productivity is corn: 2500 - 4000 kg / ha